2020
DOI: 10.3390/su12197947
|View full text |Cite
|
Sign up to set email alerts
|

How Tillage and Fertilization Influence Soil N2O Emissions after Forestland Conversion to Cropland

Abstract: Soil nitrous oxide (N2O) emissions are influenced by land use adjustment and management practices. To meet the increasing socioeconomic development and sustainable demands for food supply, forestland conversion to cropland occurs around the world. However, the effects of forestland conversion to cropland as well as of tillage and fertilization practices on soil N2O emissions are still not well understood, especially in subtropical regions. Therefore, field experiments were carried out to continuously monitor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Agricultural practices can be related to N 2 O emission based on crop yield, referred to as yield-scaled N 2 O emission (YSNE). There are many studies observed the effect of tillage operations and N fertilization on N 2 O emission in the arable land [17][18][19][20][21]. Therefore, the objective of this study was to determine the effects of different tillage operations and N fertilizations on N 2 O emission and crop yield from upland soil.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural practices can be related to N 2 O emission based on crop yield, referred to as yield-scaled N 2 O emission (YSNE). There are many studies observed the effect of tillage operations and N fertilization on N 2 O emission in the arable land [17][18][19][20][21]. Therefore, the objective of this study was to determine the effects of different tillage operations and N fertilizations on N 2 O emission and crop yield from upland soil.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that long-term N fertilizer applications could stimulate autotrophic nitrification rates 18,30,47,48 . Applying mineral N fertilizer could induce the rapid increases in NH 4 + concentrations for several weeks in cropland soils, thus providing sufficient available substrates for nitrification [49][50][51] . However, in this study, soil samples were collected once in April when several months had passed since the last fertilizer application.…”
Section: Discussionmentioning
confidence: 99%